A rare cause of cardiomyopathy in an infant: middle aortic syndrome. (14th November 2016) - Mir, Arshid; Stam, Benjamin; Sperrazza, Charles
Abstract: Coarctation of the abdominal aorta is a rare condition with a handful of cases reported in infancy. We report the case of a 4-month-old infant with severe abdominal coarctation who presented with dilated cardiomyopathy. Following successful transcatheter-based stenting of her abdominal aorta, her cardiomyopathy resolved.